PENGARUH PIJAT ENDORPHIN TERHADAP PENURUNAN RASA NYERI SAAT PROSES PERSALINAN (Jurnal Kesehatan Siliwangi, 2022)
Labor is babies expulsion process which is marked by contractions of the uterus, causing pain as long as the baby is not born. Endorphin Massage is a touch/therapy massage that is important enough to be given before the time to give birth. This is because this touch therapy stimulates the body to release endorphins which are pain relievers and can make a comfortable feeling. This evidence-based case report aimed to analyze the results of giving endorphin massage to reduce pain during the delivery process. Articles were searched through Research Gate, Portal Garuda, Crossref, and Google Scholar. One quasi-experimental article with one group pretest-posttest only by Wiwi Wardani Tanjung and Adi Antoni was appropriate to the small research to be done. Based on the appraisal, the study by Wiwi and Adi is considered valid, important, and applicable to patients. There is a difference in the intensity of labor pain in the first stage before and after endorphin massage.